Pengaruh Financial Literacy, Future Orientation, Financial Attitude, dan Financial Awareness Terhadap Perencanaan Pensiun Generasi Sandwich Di Jawa Timur - Vika Faizatul Hidayah; Ina Uswatun Nihaya (Universitas Negeri Surabaya, 2025)
This study aims to analyze the influence of financial literacy, future orientation, financial attitude, and financial awareness on retirement planning among the sandwich generation in East Java. The sandwich generation, defined as individuals who are financially responsible for both elderly parents and children, faces unique pressures that may hinder their ability to prepare for retirement. A total of 165 respondents participated in this quantitative study, and data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings show that financial literacy has a negative effect on retirement planning, while future orientation, financial attitude, and financial awareness positively influence retirement planning behavior. These results highlight that behavioral and attitudinal aspects play a more significant role in shaping retirement planning compared to general financial knowledge. The practical implications highlight the need to broaden financial education beyond technical knowledge by strengthening future orientation, positive financial attitudes, and financial awareness through accessible training and digital tools. The government, financial institutions and policymakers are encouraged to provide transparent, flexible retirement products supported by targeted incentives for individuals with dual family responsibilities, in order to enhance retirement readiness among the sandwich generation.